Collective action and social learning in integrated resource systems: Evidence from inland fisheries in Cambodia - Gleich, Pia; Baldivieso, Carla; de Silva, Sanjiv; Bonatti, Michelle (Humboldt Universitat zu Berlin, 2024)
To explore how CFRs can promote social and ecological change, we investigated two CFRs established in 2016 by local and international NGOs and authorities of the Kampong Thom Province in Cambodia. Our aim is to identify the extent to which those CFR projects support the formation of collective management and facilitate social learning processes. To do so, a qualitative case study was conducted from March to May 2023.